Reasoning Ability as a Determinant of Teaching Aptitude: A study on Teachers Trainee Student of Durg-Bhilai Region (Global Journal of Human-Social Science, 2018)
This research paper aims to highlight the importance of reasoning ability in selecting the students of teacher training colleges so that they are more likely to develop higher teaching aptitude during their training On examining the reasoning abilty score and teaching aptitude score of selected sample of student from teacher training colleges of Durg-Bhilai reason it was concluded that there was a high significant correlation between teaching aptitude and reasoning ability score of students It was also concluded that reasoning Ability was able to explain about 45 of variation in the teaching aptitude of teacher trainee students This can act as a benchmark to set entrance exam in such a way that at least 45 of the weight age is to be given to the the questions on reasoning ability